¿Fieles devotos o sodomitas “lacrientos”?: los mulatos de la cofradía de San Roque. Un sermón “inconveniente” ante el Santo Oficio novohispano, 1659 - Ursula Camba Ludlow (Centre de Recherches sur les Mondes Américains, 2012)
A preach pronounced during the celebration of San Roque festivity in the middle of the seventeenth century in Mexico City , causes various reactions that range from fury to laughter, as much in the attendants to the mass as between the viceroyal authorities. The intention of the present paper is to rescue two frankly opposed images of the black and mulattoes that were part of this brotherhood. On the one hand their devotion, commitment and care of the hospital and cofrades, that makes the preacher call them “gentlemen”. But on the other hand, few months had passed from the scandalous process that civil justice had thundered against dozens of accused men to commit the nefarious sin, same who apparently were familiar or friends of the cofrades. Then, an opposite image is given off there completely; the one of vicious sodomites and even proud and defiant. Indeed the perception of the people, priests and judges around the african descendants in this study of case, is far from being homogenous.